Using Social Media among English Major Students at Hebron University, Palestine - Farrah, Mohammed; Dabbas, Batool Hussein (Randwick International of Education and Linguistics Science Journal, 2024)
With the increasing integration of social media into educational settings, understanding its role in the lives of students has become essential. This study explores the usage patterns and perceptions of social media among English major students at Hebron University. The study has been analysed for the second semester of 2023/2024 academic year with a sample of 100 students, 74 are females and 26 are males. They are between 18 and 22. The researchers designed a questionnaire via Google Forms. Participants were given the questionnaire electronically through WhatsApp and email. Quantitative analysis techniques were used to analyse responses. SPSS program. The study suggested some recommendations that can be used at the university. The results of this research highlight the correlation between social media use and the univerity and personal lives of English major students at Hebron University.